Tailored lighting intervention (TLI) for improving sleep-wake cycles in older adults living with dementia - Figueiro, Mariana G.; Pedler, David; Plitnick, Barbara; Zecena, Erick; Leahy, Sophie (Frontiers in Physiology, 2023)
Sleep disturbance is a hallmark of Alzheimer's disease and related dementias, and caregiver stress caused by patients' nighttime wandering, injuries, and agitation are frequently at the root of decisions to move them to assisted living facilities, where typically dim institutional lighting can further exacerbate their sleep problems. This study explored the effects of a circadian-effective lighting intervention on actigraphic sleep measures and subjective assessments of sleep disturbance, depression, and sleep-disturbed behaviors. Methods: Fourteen older adult (≥60 years) participants (11 females, mean age = 84.1 [SD 8.9]), all diagnosed with moderate to severe dementia and sleep disturbance, were recruited from 3 assisted living and memory care facilities. Following a crossover, placebo-controlled design, 3 different lighting modes were used to deliver high levels of circadian stimulus to the participants' eyes for two 8week intervention periods in a counter balanced order with a 4-week washout between the study's two conditions (dim light control vs. active intervention). Actigraphy and questionnaire data were collected over 7-day assessment periods that preceded (baseline weeks 1 and 9) and concluded (post-intervention week 9 and 22) the intervention periods. Actigraphic outcomes included sleep duration, sleep time, sleep efficiency, sleep start time, and sleep end time. Subjective assessments included the Cornell Scale for Depression in Dementia (CSDD), Pittsburgh Sleep Quality Index (PSQI), and Sleep Disorders Inventory (SDI) instruments. Results: Under the active condition, sleep duration significantly (p = 0.02) increased and sleep start time significantly (p = 0.01) advanced after the intervention compared to baseline. Also under the active condition, PSQI (p = 0.01), CSDD (p = 0.01), SDI frequency (p = 0.02), and SDI severity (p = 0.02) scores were significantly lower after the intervention compared to baseline. Discussion: This study demonstrates that a circadian-effective lighting intervention delivering bright days and dark nights improves measures of sleep and mood in dementia patients living in controlled environments.